Dinamika Peran Indonesia Dalam Pusaran Konflik Palestina-Israel - Akbar, Bambang Widianto; Iskandar, Winda Nurlaily Rafikalia (JOSH: Journal of Sharia, 2025)
As is known, historically Indonesia has taken an active role in mediating the conflict between the two countries. The role taken in this case is sending peacekeeping troops to the Middle East, especially to mediate the conflict between Israel and Palestine. The background of this conflict itself began with the founding of the state of Israel in May 1948, or three years after World War II. Israel's existence in the Middle East region then sparked controversy due to their expansion in several regions, particularly their annexation of Palestinian territories. This situation then attracted international attention, various sympathy and steps taken in an effort to resolve this conflict, including Indonesia. Indonesia, which includes the principle of anti-colonialism in its constitution, also took diplomatic and humanitarian steps to resolve this, from negotiations to the deployment of peacekeeping troops. The method used in this paper is library research through data obtained through literature review techniques, which are then processed based on the formulation of the underlying problem. From this research, it was found that Indonesia took many steps and played a role in the Palestinian-Israeli conflict, regardless of the results that were later achieved